Problem-Based Learning Model to Increase Students' Science Literacy in Grade V Science Learning on Heat Transfer Topic - Srinita Susanto; Setiawan Edi Wibowo; Anisa Kurniasih; Vitry Rayani Bethesda Saragih; Annisyah Yuni (Postgraduate, University of Mataram, 2025)
This study aims to analyze the influence of the problem-based learning model on students' science literacy in science lessons in class V, especially on heat materials and their transfer. This study focuses on the pre-experimental method using a one-group pretest-posttest design research design. Data collection is carried out by providing tests consisting of pretest and posttest. Sampling technique through purposive sampling. The research sample amounted to 25 students. The data analysis technique was carried out by N-Gain and T-paired sample t-test. Based on the calculation of the hypothesis test using the t-test, it indicates that there is a significant difference between the pretest and the posttest. This can be seen from the significance value (p) = 0.000 (p < 0.05) so that the H0 hypothesis is rejected. This illustrates that the implementation of the problem-based learning model has a positive influence on students' science literacy in science lessons. Furthermore, based on the average N-Gain value of 0.5241 located in the medium group, this result indicates that the implementation of problem-based learning model is effective in improving students' science literacy in science lessons. Thus, it is concluded that the problem-based learning model has positive influence on students' science literacy. This study will contribute to the development of effective learning strategies to optimize students' science literacy and provide recommendations for educators in the application of the problem-based learning model in elementary schools.